PENTINGNYA KOMPETENSI, MOTIVASI DAN KEPUASAN KERJA MENDORONG PRESTASI KERJA - Ratnawati, Shinta; Atmaja, Hanung Eka (BBM (Buletin Bisnis & Manajemen), 2020)
Human resources are the only resources that have a sense of mind, desire, skills, knowledge, encouragement, power, and work (ratio, taste, and intention). All potential human resources affect the organization's efforts to achieve goals. The organization is a collection of people who have different competencies, which are interdependent with one another who try to realize their common interests by utilizing various resources. Basically the shared goal that the organization wants to realize is to seek profits. Therefore, it is needed employees who have high work performance through motivation, competence and job satisfaction are expected to be able to realize a successful organization.